Examining Sirtuin-1 Levels and Inflammation Markers in Behcet’s Disease: A Pilot Study - Ecesoy, Volkan; Arıcı, Hasan; Ateş, Fadime Pınar; Osmanoğlu, Usame Ömer; Ecesoy, Hilal (Archives of Rheumatology, 2025)
Background/Aims: Assess circulatory Sirtuin-1 (SIRT1) levels in Behcet’s disease (BD) and relationships with disease activity and inflammatory markers. Materials and Methods: Forty BD patients and 40 matched controls. Recorded demographics, disease activity (BDCAF), treatments, organ involvement. Measured CRP, IL-6, TNF-α, and SIRT1 in fasting blood. Results: CRP, IL-6, TNF-α higher in BD vs controls, regardless of activity. SIRT1 similar across groups and treatments. Patients with vascular + ocular involvement had lower SIRT1 than ocular only. Conclusion: Circulatory SIRT1 levels are similar in BD and controls but may associate with vascular involvement.